2021
DOI: 10.1016/j.jval.2020.12.005
|View full text |Cite
|
Sign up to set email alerts
|

When Industrial Policies Conflict With Population Health: Potential Impact of Removing Food Subsidies on Obesity Rates

Abstract: Objectives: To model the potential impact on obesity of removing butter, cheese, and sugar subsidies in the Canary Islands. Methods: A simulation model was applied based on a local data set of subsidies and retail prices (2007-2016), data on own-price elasticity estimates, and representative nutritional and health surveys. We estimated marginal obesity prevalence and population attributable fraction to assess the potential impact of the butter, cheese, and sugar subsidies intervention. Results: The interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…To date, obesity prevention and treatment strategies have not achieved long-term success at both the individual and population levels, but lifestyle and behavioral interventions such as diet nutritional pattern modi cation may have some effect on the prevention and treatment of obesity [4,5]. Cheese as an important part of the daily diet of most population in the world, several previous studies have suggested that cheese intake may play a role in reducing the incidence of obesity, but relevant conclusions were inconsistent [6][7][8][9][10]. In addition, although cheese intake may be associated with reduced incidence of obesity in previous studies using traditional epidemiological methods, the inability to fully adjust for numerous confounders was an important limitation.…”
Section: Introductionmentioning
confidence: 99%
“…To date, obesity prevention and treatment strategies have not achieved long-term success at both the individual and population levels, but lifestyle and behavioral interventions such as diet nutritional pattern modi cation may have some effect on the prevention and treatment of obesity [4,5]. Cheese as an important part of the daily diet of most population in the world, several previous studies have suggested that cheese intake may play a role in reducing the incidence of obesity, but relevant conclusions were inconsistent [6][7][8][9][10]. In addition, although cheese intake may be associated with reduced incidence of obesity in previous studies using traditional epidemiological methods, the inability to fully adjust for numerous confounders was an important limitation.…”
Section: Introductionmentioning
confidence: 99%